2017
DOI: 10.1523/jneurosci.3000-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Distribution of HDAC1 in Neurotoxic Conditions Is Dependent on Serine Phosphorylation

Abstract: Calcium-dependent nuclear export of histone deacetylase 1 (HDAC1) was shown previously to precede axonal damage in culture, but the in vivo relevance of these findings and the potential posttranslational modifications of HDAC1 remained elusive. Using acute hippocampal slices from mice of either sex with genetic conditional ablation of Hdac1 in CA1 hippocampal neurons (i.e., Camk2a-cre;Hdac1 fl/fl ), we show significantly diminished axonal damage in response to neurotoxic stimuli. The protective effect of Hdac1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…In that same study, the authors show that decreasing HDAC1 levels by genetic ablation was neuroprotective against acute neurotoxicity in hippocampal slices. The protective effect of Hdac1 ablation was also detected in CA3 neurons in mice, which were more resistant to the excitotoxic damage induced by intraventricular injection of kainic acid (Zhu et al 2017).…”
Section: Neurotoxic Effects Of Hdac1mentioning
confidence: 86%
See 2 more Smart Citations
“…In that same study, the authors show that decreasing HDAC1 levels by genetic ablation was neuroprotective against acute neurotoxicity in hippocampal slices. The protective effect of Hdac1 ablation was also detected in CA3 neurons in mice, which were more resistant to the excitotoxic damage induced by intraventricular injection of kainic acid (Zhu et al 2017).…”
Section: Neurotoxic Effects Of Hdac1mentioning
confidence: 86%
“…The protective effect of Hdac1 ablation was also detected in CA3 neurons in mice, which were more resistant to the excitotoxic damage induced by intraventricular injection of kainic acid (Zhu et al . ).…”
Section: Hdac1mentioning
confidence: 97%
See 1 more Smart Citation
“…So far, the endothelial phenotype in CKD has been extensively characterized, but there is a lack of information regarding the mechanisms through which the uraemic milieu exerts an impact on the endothelial cell and its epigenome. In this sense, several studies have shown that HDAC1 can also be expressed in the cytosol in different cell lines, [38][39][40] and although its expression is mainly located in the nucleus, its expression is enhanced in the cytosol in pathological conditions. We were able to identify two proteins, HDAC1 and HDAC2, involved in epigenetic regulation, among other up-regulated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stimuli of interstitial flow stimulated HDAC1 phosphorylation and increased the localization of phosphorylated HDAC1 (p-HDAC1) to the cytoplasm (38). Intracellular Ca 2+ inhibited nuclear localization and phosphorylation of HDAC1 (39,40). Here, the subcellular localization of p-HDAC1 was investigated by analyzing the fluorescence intensity of immunostained p-HDAC1 in cytosol and nuclei ( Fig.…”
Section: The Role Of Mechanical Stimuli and Intracellular Ca 2+ On Yamentioning
confidence: 99%